Essential oil composition of two endemic Tanacetum (T. nitens (Boiss.&Noe) Grierson and T. argenteum (Lam.) Willd. subsp argenteum) (Asteraceae) taxa, growing wild in Turkey - Bagci, Eyup; Kocak, Alpaslan (Elsevier, 2010)
The genus Tanacetum includes some popular endemic species of the flora of Turkey, with important medicinal properties. Some members of this genus have traditionally been used in balsams, cosmetics, dyes, insecticides, medicines and preservatives as herbal remedy. Information about the essential oil compositions of Tanacetum nitens (Boiss.&Noe) Grierson and T. argenteum (Lam.) Willd. subsp. argenteum Turkish medicinal plants has not been reported. For this reason the objective of this study was to determine the chemical composition of the essential oils of dried aerial parts of two endemic Tanacetum taxa. The plants were collected from natural habitats in Baskil and Harput (Elazig), in 2008. Chemical analyses were performed by GC and GC-MS assays. Forty-two and forty-eight components were identified representing 87.97% and 88.10% of the oils, respectively. The main compounds were 1,8-cineole (27.57%), alpha-pinene (4.62%), spathulenol (4.14%) and trans-pinocarveol (4.13%), whereas alpha-pinene (27.86%), santolinatriene (8.82%), 1,8-cineole (6.82%), chrysanthenone (3.83%), cadina-1,4-dien and beta-pinene (3.16%) were the major constituents of T. argenteum subsp. argenteum. It was concluding that the essential oils: 1,8-cineole chemotype in T. nitens and alpha-pinene chemotype in T. argenteum subsp. argenteum was in plants from eastern Anatolian region of Turkey. These essential oils can be used as raw material in medicinal and pharmaceutical purposes. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Tanacetum nitens; Tanacetum argenteum subsp argenteum; Asteraceae; GC-MS; Essential oil